Increasing The Students’ Learning Activity and The Students’ Derivation Words Mastery Using The Memory Strategies at Second Grade s in University of Bina Sarana Informatika - Rahayuningsih, Retno; Rosalinah, Yanti; Subroto, Ibnu (Universitas PGRI Semarang, 2024)
The objective of this research was to know whether memory strategy can increase the student’s learning activity and to increase the student’s derivation words mastery. The subject of this research was the students of Second grade student in university of Bina Sarana Informatika. The research used the classroom action research which was done in 2 cycles. Every cycle consists of 4 steps: planning, action, observation, and reflection or evaluation. In collecting data, the researcher used test, observation, and fill note, whereas, to analyze the data, the researcher used the percentage formula, the average, and the increasing. Based on the research result which was taken from the observation and test, it can be inferred that: (1) Memory strategy can increase the students learning activity it can be seen in the percentage increasing of the students learning activity of cycle 1 to cycle II: the indicator increasing of paying attention to the teacher explanation is 18%, the indicator increasing of answering the questions is 21%, the indicator increasing of giving the idea is 9%, the indicator increasing of asking the teacher is 15%, the indicator increasing of note is 14%, the indicator increasing of doing the group task and being active in the group is 27%. (2) Memory strategy can increase the students’ derivation word mastery. It can be seen in the result increasing of posttest 2 in the cycle II. (a) The average score increasing of pre-test to posttest 1 cycle I is 1.4 and the average score increasing of posttest 1 in cycle I to posttest 2 in cycle II is 1.7, (b) Based on the Minimum Requirement Criteria the students in the complete category is 77% and the students in the incomplete category are 23%. Therefore, the English learning. Process in affix material by using the memory strategies had been successful, because the students in the complete category are more than 75%.